Measurement, Correlation and Thermodynamics of Solubility of 2, 6‐Diamino‐3, 5‐Dinitropyrazine‐1‐Oxide (LLM‐105) in Eight Solvents. Issue 12 (4th December 2017) - Bu, Rupeng; Zhou, Xiaoqing; Huang, Qi; Yu, Yanwu; Li, Hongzhen
Abstract: The solubility of insensitive explosive 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) in dimethyl sulphoxide (DMSO), N, N‐dimethylformamide (DMF), N‐methyl‐2‐pyrrolidone (NMP), N, N‐diethylformamide (DEF), 1, 4‐dioxane, 1, 4‐butyrolactone, ethyl acetate and 1‐butyl‐3‐methylimidazolium trifluoromethanesulfonate ([Bmim]CF3 SO3 ), were measured by a polythermal method in the temperature range of 293.15 K to 375.15 K at the atmospheric pressure. The solubility of LLM‐105 decreased in the order of DMSO, NMP, DMF, DEF, 1, 4‐butyrolactone, [Bmim]CF3 SO3, 1, 4‐dioxane, ethyl acetate. With higher temperature, the solubility of LLM‐105 increased in all solvents. The solubility data was correlated against temperature with the modified Apelblat equation and Ideal solution model. In addition, the dissolution enthalpy, entropy, and mole Gibbs free energy of LLM‐105 in each solvent were also calculated from the experimental solubility data by using van′t Hoff equation with the temperature dependence. The results show that the dissolution process of LLM‐105 in these solvents is endothermic and the mechanism is the entropy‐driving. DMSO is suggested as the appropriate solvent for the cooling crystallization or drowning‐out crystallization of LLM‐105. Abstract :